The benefit of H2 receptors antagonist Rupatadine in treatment for urticaria - A. A. Kubanov; V. V. Chikin (Vestnik Dermatologii i Venerologii, 2017)
Second generation antihistamine drugs are mainly used for the therapy of patients suffering from urticaria; however, they are efficient in 45-60% of cases only. New drugs for treatment of urticaria need to be developed and implemented, and second generation antihistamine drug Rupatadine is one of them. At the same time, Rupatadine efficiently inhibits the inflammatory action of the platelet-activating factor. Due to its double action, Rupatadine used perorally in the dose of 10 mg once a day is an efficient drug for treatment of urticaria, and its safety was confirmed by clinical trials.